Pengaruh Periode dan Media Penyimpanan Entres terhadap Keberhasilan Okulasi Hijau dan Kandungan Air Entres pada Tanaman Karet - Saefudin Saefudin; Edi Wardiana (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Proper storage period and medium is essential in order to keep the scion of rubber plant in a good condition, so that the budding success rate can still be maintained as high as possible. The objective of this study was to determine the effect of storage periods and media of scion on the success level of green budding and its water content in the rubber plant. This experiment was conducted at Pakuwon experimental garden with altitude of 450 m above sea level, Latosol type of soil, and B type of climate according to the classification of Schmidt and Fergusson, from January to July 2014. Randomized complete block design in single factor with nine treatments and three replications was used in this study. The nine treatments used were: (1) storage of scion for 2 days without media, (2) Two days stored with moistened newsprint paper, (3) Two days stored with moistened sawdust media, (4) Two days stored with moistened cocopeat media, (5) Four days stored without media, (6) Four days stored with moistened newsprint paper, (7) Four days stored with moistened sawdust media, (8) 4 days stored with moistened cocopeat media, and (9) without storing/control (K). The results showed that the storage of rubber scion for 2-4 days can reduce the success level of green budding due to the decrease in water content of scion. In condition when scion had to be stored, it should be a maximum of 4 days by using moistened newspapers or sawdusts storage media. Both of the storage media can still maintain the water content of scion at about 94.8% and 93.9%, respectively, compared to the water content of scion without storage treatment.